If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = 9x + 3 Reorder the terms: 7 + 3x = 9x + 3 Reorder the terms: 7 + 3x = 3 + 9x Solving 7 + 3x = 3 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 7 + 3x + -9x = 3 + 9x + -9x Combine like terms: 3x + -9x = -6x 7 + -6x = 3 + 9x + -9x Combine like terms: 9x + -9x = 0 7 + -6x = 3 + 0 7 + -6x = 3 Add '-7' to each side of the equation. 7 + -7 + -6x = 3 + -7 Combine like terms: 7 + -7 = 0 0 + -6x = 3 + -7 -6x = 3 + -7 Combine like terms: 3 + -7 = -4 -6x = -4 Divide each side by '-6'. x = 0.6666666667 Simplifying x = 0.6666666667
| 3n-5=-21 | | 33.33333=4+-1 | | c=0.75y+50 | | x+26=2x+4 | | 2x+y=110 | | (Y-6)-(y+6)=7y | | Y=ln(e^7x) | | 4x-10=-60-10x | | 41-5x=14-8x | | x+(x*0.28)=100 | | 10+6x=-15+x | | 3x-9=x+27 | | Ln(x-3)= | | -(-1k+1)=-5(1-6k)+7k | | b+3=3 | | y-9=-17 | | 4.8x+38.3=10.9-8.9x | | 1/3x-5/6=1/9x | | sqrt(2x^2-5x-3)=x+1 | | 15x^2+3x= | | x+sqrt(25-x^2)=7 | | 5y*2y-3= | | x^2+sqrt(25-x^2)=7 | | 2(x+1)+3x+6=4 | | 15x-7=-2 | | t^2+4t+3=0 | | 28=2x+2 | | 3lnx^6-2lnx^2=14 | | 3ln(x^6)-2ln(x^2)=14 | | 3x-9x+5x-7x= | | cos^2x-sen^2x=0 | | 0.025p-2=0.15(p-5) |